Pengaruh Beberapa Jenis Pupuk Hayati terhadap Pertumbuhan Dua Klon Tanaman Teh (Camellia sinensis (L) O. Kuntze) Belum Menghasilkan - Ade Wachjar; , Supijatno; Dina Rubiana (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
The experiment was carried out to study the effect of biofertilizer on the growth of  two clones of young tea. This experiment was conducted at Cikabayan Experiment Station, Faculty of Agricuture, IPB, Bogor, from July to November 2000. This experiment was arranged in Split Plot Design with three replications.  The main factor was clone types consisted of two clones i.e.: RB 3 and Gambung 5, whereas the sub factor was biofertilizer consisted of five kinds i.e. : EMAS + 50 % inorganic fertilizer recommended dosage (i.f.r.d.), EM4 + 50 % i.f.r.d., OST + 50 % i.f.r.d., Soils Plus + 50 % i.f.r.d. and 100 % i.f.r.d. The results showed that the EMAS + 50 % i.f.r.d. and EM4 + 50 % i.f.r.d. treatments significantly increased plant height, stem diameter, leaf number, and bud length.  The application of 6.25 g EMAS per plant (equivalent with 83.125 kg/ha) + 50 % i.f.r.d.  and  10 ml  EM4 (equivalent with 6.65 l/ha) + 50 %  i.f.r.d.  could reduce  application of  inorganic  fertilizer dosage until 50 % and resulted in  the growth of the plant which  was better than that of inorganic fertilizer. In  general,  growth of the RB 3 clone was better than Gambung 5 clone.   Key words :  Biofertilizer, clones, vegetative  growth, tea